القيم التنظيمية و علاقتها بأساليب إدارة الصراع التنظيمي لدى عينة من موظفي ديوان مؤسسات الشباب و الرياضة - محامدية, الأمين (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2016)
هدفت الدراسة إلى الكشف عن العلاقة بين القيم التنظيمية المتمثلة في (قيمة التعاون و الانتماء و الانضباط و العدالة) و أساليب إدارة الصراع الخمسة ( التعاون، التنافس، التوسط، التنازل، التجاهل). ولتحقيق أهداف الدراسة استخدمنا المنهج الوصفي، وتكونت عينة الدراسة من (40) موظف بنسبة ) %100 ) من المجتمع الأصلي. و قد أجريت هذه الدراسة في مؤسسة ديوان الشباب و الرياضة بالمسيلة، و تم جمع البيانات و المعلومات من خلال استبيان صمم خصيصا لدراسة موضوع القيم التنظيمية، بالإضافة إلى استخدام مقياس توماس و كولمان لقياس أساليب إدارة الصراع التنظيمي. و خلصت الدراسة إلى النتائج التالية: 1. توجد علاقة إرتباطية ذات دلالة إحصائية بين القيم التنظيمية و أساليب إدارة الصراع التنظيمي لدى عينة من موظفي ديوان الشباب و الرياضة بالمسيلة. 2. توجد علاقة إرتباطية ذات دلالة إحصائية بين القيم التنظيمية و أسلوب التعاون لدى عينة من موظفي ديوان مؤسسات الشباب و الرياضة بالمسيلة. 3. توجد علاقة إرتباطية ذات دلالة إحصائية بين القيم التنظيمية و أسلوب التنافس لدى عينة من موظفي ديوان مؤسسات الشباب و الرياضة بالمسيلة. 4. توجد علاقة إرتباطية ذات دلالة إحصائية بين القيم التنظيمية و أسلوب التوسط لدى عينة من موظفي ديوان مؤسسات الشباب و الرياضة بالمسيلة. 5. توجد علاقة إرتباطية ذات دلالة إحصائية بين القيم التنظيمية و أسلوب التنازل لدى عينة من موظفي ديوان مؤسسات الشباب و الرياضة بالمسيلة. 6. توجد علاقة إرتباطية ذات دلالة إحصائية بين القيم التنظيمية و أسلوب التجاهل لدى عينة من موظفي ديوان مؤسسات الشباب و الرياضة بالمسيلة. Summary of the study : The study aimed to detect the relationship between organizational values of ( the value of cooperation, affiliation, discipline, justice ) and styles of Conflict Management five ( cooperation, Competition, mediate, Waiver, ignore ). To realize the study objectives the researcher applied the descriptive method , Study sample included (40) person with percentage (100%) of all study population. This study was conducted at institution of Youth and Sports in m’sila, Then collect the data and information Through a questionnaire Designed specifically for the study of organizational values, In addition to using Thomas Coleman scale for measure the organizational conflict management techniques, The study comes to the following findings: 1. There is positive link relationship with statistical significance between Organizational values and methods used in the management of organizational conflict at of Youth and Sports institution staff in m’sila. 2. There is positive link relationship with statistical significance between Organizational values and the style of cooperation at of Youth and Sports institution staff in m’sila. 3. There is positive link relationship with statistical significance between Organizational values and the style of Competition at of Youth and Sports institution staff in m’sila. 4. There is positive link relationship with statistical significance between Organizational values and the style of mediate at of Youth and Sports institution staff in m’sila. 5. There is positive link relationship with statistical significance between Organizational values and the style of waiver at of Youth and Sports institution staff in m’sila. 6. There is positive link relationship with statistical significance between Organizational values and the style of ignore at of Youth and Sports institution staff in m’sila
Keywords: القيم التنظيمية و علاقتها بأساليب إدارة الصراع التنظيمي لدى عينة من موظفي ديوان مؤسسات الشباب و الرياضة